Blacksmiths without frontiers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Many innovative attempts have been made by local artisans to market their small-scale manufacture of hand tools and workshop equipment.How about promoting their products on the World Wide Web? That s what several small businesses have done in...